Innovation of Language Receptive Skills Based on Authentic Assessment - R Umi Baroroh; Faizmailiatus Sofa; Putri Nurinadia; Nur Wahidah; Syifa Nurul Afifah (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
The purpose of this scientific study is to analyze and answer the problems that exist in the assessment of class XI Arabic books published by the Ministry of Religion of the Republic of Indonesia in 2020, especially on language receptive skills, which consist of listening and reading skills. This research was studied using qualitative methods and literature studies to collect data. Primary data comes from Arabic books published by the Ministry of Religion in class XI in 2020, while secondary data comes from literature documents that are relevant to the research. The results of the analysis show that receptive language skills have been assessed and are included in the realm of knowledge. In fact, receptive skills (reading and listening) must be included in language skills, while aspects of language knowledge can be obtained from language elements. Therefore, an authentic assessment is needed that positions receptive skills in the assessment of skills, which at the same time can assess linguistic elements in the knowledge aspect without forgetting the attitude aspect by assessing portfolios, assignments, performance, and interviews that are tailored to needs. The theme of the text being read or heard. Authentic assessment of receptive skills can be carried out by using projects, interviews, or assignments with command words, such as concluding the spoken text heard, making pictures based on the description of the spoken text, making conversations according to the content heard, or making texts that are similar to the text being spoken heard.